Family jewels - Woods, Stuart (Woods, Stuart. Stone Barrington novel, 2016)
"Stone Barrington is back and better than ever in the newest thriller from the #1 New York Times-bestselling author. Stone Barrington's newest client seems to be a magnet for trouble. A poised lady of considerable wealth, she's looking for help discouraging the attentions of a tenacious gentleman. But no sooner does Stone fend off the party in question than his client becomes involved in two lethal crimes. With suspects aplenty, Stone must probe deep into his client's life to find the truth, and he discovers that the heart of the mystery may be a famous missing piece of history, a stunningly beautiful vestige of a bygone era. It's a piece with a long and storied past and untold value. the kind of relic someone might kill to obtain. Among the upper crust nearly everyone has buried a skeleton or two, and it will take all of Stone's investigative powers to determine whose secrets are harmless, and whose are deadly"--